The Relationship of Self-Efficacy and Social Support on Work-Family Balance - Hasna, Afra; Wibowo, Mungin Eddy; Mulawarman, Mulawarman (Islamic Guidance and Counseling Journal, 2020)
This study conducted based on the phenomenon of complex problems faced by the students who have dual roles, namely students who are married and also working. The study aims to find out the empirical data and to ensure the relationship between self-efficacy and social support with work-family balance. The research design used a correlation with the ex-post-facto model that had 214 samples were selected using purposive sampling techniques with the criteria of students who were married and also working. The data assessed by using the General Self-efficacy (GSE) Scale, Multidimensional Scale of Perceived Social Support (MSPSS), and Work-Family Balance Scale (WFBS). The data analyzed by using hierarchical regression analysis techniques. The results showed that: 1) there was a significant relationship between self-efficacy and work-family balance (∆R=0.351; ∆F=63.927; P=<0.01) with a contribution of 22.8%, 2) there was a significant relationship between social support and work-family balance (∆R=0.145; P<0.01) with a contribution of 16.6% based on the significant aspects of other support, family support, and friend support, the results obtained significant relationships in each aspect of family support and friends’ support with work-family balance, and 3) there was a significant simultaneous relationship between self-efficacy and social support with family balance (R=0.645; F=24.618; P<0.05) with the most frequent based on R2 for 41.6%. This study concluded that there is a partially and simultaneously significant relationship between self-efficacy, social support, and work-family balance. The implications of these findings are discussed in the discussion.